Electrochemical measurement of endogenously produced nitric oxide in brain slices using Nafion/o-phenylenediamine modified carbon fiber microelectrodes - Ferreira, Nuno R. (2005)
The role of nitric oxide (NO) as a regulatory diffusible molecule in the brain requires the evaluation of its concentration dynamics. In this work, we have developed microelectrodes suitable for real time electrochemical measurements of NO in vitro. Nafion and o-phenylenediamine were used to modify the surface of carbon fiber microelectrodes (8 [mu]m diameter; [approximate]100 [mu]m tip length). Coating with Nafion was done at 170 °C and the o-phenylenediamine solution was electropolimerized on the carbon surface. NO peak potential (+0.78 ± 0.03 V versus Ag/AgCl) was determined by square wave voltammetry with NO solutions prepared from the-generating compound diethylenetriamine/nitric oxide (DETA/NO). Microelectrodes were calibrated by amperometry at a potential of +0.90 V versus Ag/AgCl. They showed good sensitivity (954 ± 217 pA/[mu]M; n = 6) and linearity to NO in the concentration range of 100-1000 nM. They were also characterized in terms of detection limit (6 ± 2 nM, n = 4), response time at 50% (1 s), and selectivity against interferents, such as nitrite (780 ± 84:1, n = 6), ascorbic acid (750 ± 187:1, n = 6) or dopamine (18 ± 2:1, n = 6). Injections of 1 mM l-glutamate, 1 mM l-arginine, and 0.1 mM N-methyl-d-aspartate did not produce changes in background current. Finally, the microelectrodes were used to measure NO concentration dynamics in rat hippocampal brain slices stimulated with l-glutamate and N-methyl-d-aspartate. Taken together, the data indicate that the microelectrodes exhibit the proper sensitivity and selectivity for studies of NO dynamics in brain slices (in vitro) and possibly in whole brain (in vivo) recordings.